Development and Optimization of a Differential Signal-Based Fabry-Perot Interferometer for Nanopositioning - Syuan-Cheng Chang; Chung-Ping Chang; Yung-Cheng Wang (Tehnički Glasnik)
In this study, we present the optimization of a Fabry-Perot interferometer with a differential signal utilized as the laser encoder to meet the stringent demands of nanopositioning. The proposed system aims to enhance stability and accuracy in nanopositioning applications by leveraging the common path structure and coaxial characteristics of Fabry-Perot interferometers. To improve the resolution of this system, an interpolation module is employed to increase the laser encoder resolution to 15.82 nm. Compared to the simulated interference signal from traditional Fabry-Perot interferometers, the differential interference signal proposed in this study is more sinusoidal, thus reducing errors in resolution subdivision. To verify the correspondence between the actual interference signal and the simulated one, a signal testing experiment is implemented in this study. Eventually, the experimental signal results demonstrate that the actual light intensity signals match the simulated results, indicating that this signal can be significantly beneficial for use as a laser encoder.